2008
DOI: 10.1007/s11920-008-0010-9
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent depression and emergency department use: The roles of suicidality and deliberate self-harm

Abstract: Depression is associated with increased health service use; clarifying the processes involved may offer strategies to reduce the disorder's individual and societal burdens. This review hypothesizes roles for suicidality and deliberate self-harm to partially explain a relationship between adolescent depression and increased emergency department use. Briefly, depression is associated with suicidality and deliberate self-harm, both of which are likely common among emergency department presentations in this age gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…However, not much research attention has focused on comparing the association between CVD comorbidity and psychiatric diseases by specific age groups. Until recently, only a few studies focusing on cardiovascular disease in adolescents with psychiatric illness have shown that the correlation is strong 32–38 . Interestingly, our results showed that when compared with entire insured populations without mood or anxiety disorders and stratified with age groups, the RR of developing IHD and hypertensive diseases was found to be highest in study participants below 20 years; and this held true for all diagnosis of MDD, BD and AD during the 4‐year period.…”
Section: Discussionsupporting
confidence: 50%
“…However, not much research attention has focused on comparing the association between CVD comorbidity and psychiatric diseases by specific age groups. Until recently, only a few studies focusing on cardiovascular disease in adolescents with psychiatric illness have shown that the correlation is strong 32–38 . Interestingly, our results showed that when compared with entire insured populations without mood or anxiety disorders and stratified with age groups, the RR of developing IHD and hypertensive diseases was found to be highest in study participants below 20 years; and this held true for all diagnosis of MDD, BD and AD during the 4‐year period.…”
Section: Discussionsupporting
confidence: 50%
“…This utilization may stem, in part, from the higher prevalence of psychiatric disorders among lower income groups with limited access to mental health care treatment [ 23 ]. Patient depressive symptoms also contribute to increases emergency department utilization as suicidality and deliberate self-harm are both common among presentments [ 17 , 22 , 24 28 ]. Thus, case management for psychosocial problems, homelessness, and substance abuse among frequent users may decrease emergency department use while improving patient care [ 29 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…As adults with psychological problems tend to use more health services, leading to greater costs [12,13], understanding the pattern and association between mental illness and health-care utilization becomes important. Emergency department (ED) services are of particular interest since, relative to primary or specialty care, emergency care and any subsequent inpatient care are costly, and because the rate of psychiatric-related emergency department visits increased by 15% between 1992 and 2000 [14].…”
Section: Introductionmentioning
confidence: 99%